Alternative friction stir welding technology for titanium–6Al–4V propellant tanks within the space industry. (19th May 2017) - Brassington, W. D. P.; Colegrove, P. A.
ABSTRACT: Friction stir welding (FSW) offers an appealing solid state joining alternative to traditional fusion welding techniques for titanium alloys because it reduces problems associated with high temperature processing. Propellant tanks are a critical component of every spacecraft and contain several weld seams and a prime candidate for this innovative technology. This paper reviews the current technological maturity of FSW relative to titanium alloys and considers the application with respect to a pressure vessel. FSW is currently in a period of significant investment by large engineering companies and international research institutions. The technology is advancing and evolving to cater for high temperature alloys. Stationary shoulder FSW and hybrid techniques show promising potential with respect to Ti–6Al–4V. The tool material and limited process window for this material are restrictive factors at present but can be overcome with future development.